Development of microstructure during the hot plastic deformation of high clean steels for power plants - Kuskulic, Tomas (Materiali in tehnologije, 2008)
The effect of the deformation and the deformation temperature on the primary austenite grain size, the recrystallisation and the mechanical properties of high clean steel STN 41 6537 (STN standard) were investigated. This steel grade is used for the forged rotors of steam turbines in power-generation facilities.
Keywords: jeklo; kovanje; rekristalizacija; mehanske lastnosti